2018
DOI: 10.1111/ijpp.12456
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of the pharmaceutical care needs of people with sensory loss

Abstract: Objectives This scoping review collated evidence of the pharmaceutical care needs of people with sensory loss (SL). Methods Electronic databases were searched with no limit on year of publication: Medline (1946); Embase; Cinahl (1979); and Web of Science (1985). Search terms included the following: pharmacy; sight/hearing/dual impairment. Studies were included if they involved people with SL requiring pharmaceutical care and/or pharmacists/pharmacy support staff providing pharmaceutical care for people with SL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…15 16 A recent scoping review (conducted by the authors of this study) identified 11 studies which demonstrated that people with sensory loss had lower levels of medication knowledge and were at higher risk of iatrogenic harm compared with people without sensory loss. 16 For example, one cross-sectional survey evaluating practising pharmacists’ attitudes towards and methods of interacting with deaf patients in the USA reported that two-thirds of community pharmacy personnel were not comfortable interacting with patients with hearing impairment because of communication difficulties. 17 Commonly used methods for communication with individuals with hearing or visual impairment included hearing loops and large print resources, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…15 16 A recent scoping review (conducted by the authors of this study) identified 11 studies which demonstrated that people with sensory loss had lower levels of medication knowledge and were at higher risk of iatrogenic harm compared with people without sensory loss. 16 For example, one cross-sectional survey evaluating practising pharmacists’ attitudes towards and methods of interacting with deaf patients in the USA reported that two-thirds of community pharmacy personnel were not comfortable interacting with patients with hearing impairment because of communication difficulties. 17 Commonly used methods for communication with individuals with hearing or visual impairment included hearing loops and large print resources, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…There were no studies that met the inclusion criteria for this review, which was not unexpected. The review by Killick et al, that was published shortly after our search had been completed, highlighted the lack of intervention studies to enhance pharmaceutical care for people with sensory loss [9]. The systematic review by Beverly et al [31] on health information needs of visually impaired people identified only a few studies, most of which were of poor quality.…”
Section: Discussionmentioning
confidence: 99%
“…Beverley et al interviewed 31 visually impaired people and found that only a small proportion of health and social care needs were being met, and participants had many information needs including those related to techniques for administering medicines and reading medical information [8]. A recent scoping review of the pharmaceutical care needs of people with sensory loss (hearing and/or vision loss) highlighted the paucity of studies examining the pharmaceutical care needs of this population [9]. Challenges to medicines use experienced by those who are visually impaired include problems with distinguishing between medicines, doses and expiration dates as well as adherence issues [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ling et al [5] noted the challenges of medication handling among the visually impaired population. Killick et al [6] reviewed the scope of the pharmaceutical care needs of sensory-impaired people. Alhusein et al [7] performed a multiple-method study on the medical care requirements of sensory-impaired elderly people in the polypharmacy context.…”
Section: Introductionmentioning
confidence: 99%